Rapid Conversion from Clinic to Telehealth Behavioral Services During the COVID-19 Pandemic - Crockett, Jennifer L. (Behav Anal Pract, 2020)
Survival often depends on behavior that can adapt to rapid changes in contingencies, which should be particularly well suited to a contingency-sensitive and data-based discipline such as applied behavior analysis (ABA). The speed and scale with which contingencies shifted in early March 2020 due to the effects of COVID-19 represent a textbook case for rapid adaptation with a direct impact on the survival of many types of enterprises. We describe here the impact, changes, and outcomes achieved by a large, multifaceted ABA clinical program that has (a) ongoing data that forecasted and tracked changes, (b) staff well practiced with data-based shifts in operations (behavior), and (c) up-to-date information (data) on policy and regulations. The results showed rapid shifts in client and staff behavior on a daily basis, shifts in services from in-person services to telehealth, and increases in volumes, revenue, and margins. We detail regulations and provide actionable steps that clinical organizations can take pertinent to this shift now and in the future. The challenges of the COVID-19 pandemic underscore the importance of maintaining robust coordination and communication across our field in order to address crises that affect our field.